Terlipressin & Albumin Therapy in Hepatorenal Syndrome: A Comparative Analysis of Renal Function and Survival Outcomes - HAIDER, ALI SAQLAIN; ABDUL MATIN QAISAR,; HUMAIRA SAMI ULLAH,; NEHA AHUJA,; ABAD-UR-REHMAN,; KASHIF RIAZ, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Hepatorenal syndrome is a syndrome of critical and life-threatening complications of advanced liver cirrhosis in which the renal dysfunction is not caused by underlying kidney disease. Telipressin in combination with albumin is also involved in enhancing renal dysfunction and survival in patients with hepatorenal syndrome. Objective: To determine the effect of terlipressin and albumin on the improvement of renal functions, survival and adverse events in patients with hepatorenal syndrome type 1 and 2. Methods: It was a retrospective cohort study that was conducted on 188 subjects, i.e., patients with hepatorenal syndrome who were prescribed with terlipressin (1 mg per 4 hours) and albumin (20-40 g per day) during the period 1st July 2024 and 28th March 2025 at the Department of Nephrology, University College of Medicine and Dentistry, The University of Lahore. Renal improvement in terms of a 30% decrease of serum creatinine was set as the main endpoint. Secondary outcomes were 30 and 6-month survival and the occurrence of adverse events. Results: 45 % had hepatorenal syndrome type 1 and 55 percent had hepatorenal syndrome type 2. Renal performance improved in 62 percent of patients and 35 percent recovered their renal functions completely. The 30 days and 6 months mortality rates were 15 and 30 percent, respectively. The combination therapy was associated with a significant reduction of mortality in patients with type 1 hepatorenal syndrome (p=0.04). The number of adverse events was 13 percent in both hypertension and ischemic events. Conclusion: Terlipressin combined with albumin is of significant benefit in enhancing renal activity and survival in patients with hepatorenal syndrome when administered in combination with albumin, and in patients with type 1 hepatorenal syndrome. The timing of treatment is very important to achieve good results.